Exchange Rate Flexibility and Credit during Capital Inflow Reversals : Purgatory ... not Paradise - Magud, Nicolas (IMF Working Papers; Working Paper, 2014)
We document the behavior of macro and credit variables during episodes of capital inflows reversals in economies with different degrees of exchange rate flexibility. We find that exchange rate flexibility is associated with milder credit growth during the boom but, even though smaller than in more rigid regimes, it cannot shield the economy from a credit reversal. Furthermore, we observe what we dub as a recovery puzzle: credit growth in economies with more flexible exchange rate regimes remains tepid well after the capital flow reversal takes place. This results stress the complementarity of macro-prudential policies with the exchange rate regime. More flexible regimes could help smoothing the credit cycle through capital surchages and dynamic provisioning that build buffers to counteract the credit recovery puzzle. In contrast, more rigid exchange rate regimes would benefit the most from measures to contain excessive credit growth during booms, such as reserve requirements, loan-to-income ratios, and debt-to-income and debt-service-to-income limits.